Ethnic-immigrants in founding teams: Effects on prospector strategy and performance in new Internet ventures - Chaganti, Rajeswararao (Raj) S.; Watts, Allison D.; Chaganti, Radha; Zimmerman-Treichel, Monica (Journal of Business Venturing, 2008)
We investigated differences in strategy and performance between new Internet ventures with ethnic-immigrant members in the founding team and a matched set of Internet ventures with non-ethnic-non-immigrant team members. Results showed that new ventures with an ethnic-immigrant presence in the founding teams tended to pursue a more aggressive prospector strategy than those with non-ethnic-non-immigrant founding team members. Still, performance of the two groups of ventures was comparable. However, the positive effects of ethnic-immigrant presence on founding teams depended on team size and average age of the founding team members.